Electrification of Experimental Volcanic Jets with Varying Water Content and Temperature. Issue 20 (30th October 2019) - Stern, S.; Cimarelli, C.; Gaudin, D.; Scheu, B.; Dingwell, D.B.
Abstract: Volcanic lightning—a near ubiquitous feature of explosive volcanic eruptions—possesses great potential for the analysis of volcanic plume dynamics. To date, the lack of quantitative knowledge on the relationships between plume characteristics hinders efficient data analysis and application of the resulting parameterizations. We use a shock‐tube apparatus for rapid decompression experiments to produce particle‐laden jets. We have systematically and independently varied the water content (0–27 wt%) and the temperature (25–320 °C) of the particle‐gas mixture. The addition of a few weight percent of water is sufficient to reduce the observed electrification by an order of magnitude. With increasing temperature, a larger number of smaller discharges are observed, with the overall amount of electrification staying similar. Changes in jet dynamics are proposed as the cause of the temperature‐dependence, while multiple factors (including the higher conductivity of wet ash) can be seen responsible for the decreased electrification in wet experiments. Plain Language Summary: Volcanic explosive eruptions are accompanied by lightning strikes generated from the volcanic dust cloud. Here we have experimentally studied the effects of atmospheric water and plume temperature on the frequency and intensity of the lightning strikes. The results will feed a model for the use of volcanic lightning strikes to estimate plume contents and intensity. Key Points: Natural observations on the influence of temperature and water content on volcanic lightning have been modelled in laboratory experiments. The magnitude of electrification and discharging in plumes decreases significantly with added water. At higher temperatures a decrease in magnitude of individual discharges is observed, while the total neutralized charge stays similar.